Leveraging translational approaches for accelerated clinical development of vericiguat. (14th October 2021) - Meyer, M; Schneckener, S; Loosen, R; Coboeken, K; Willmann, S; Burghaus, R; Lippert, J; Mueck, W; Becker, C
Abstract: Background/Introduction: Vericiguat is a soluble guanylate cyclase (sGC) stimulator, like riociguat and nelociguat, and entered clinical development in 2012. Before entering Phase 2, pharmacokinetics (PK) and pharmacodynamics (PD) of vericiguat had been studied in healthy volunteers only, whereas riociguat and nelociguat had also been studied in patients with pulmonary hypertension (PH) and left ventricular dysfunction (LVD) or biventricular chronic heart failure (HF). We hypothesised that integrating all PK/PD data from these compounds into population PK/PD (popPK/PD) and physiology-based PK (PBPK) models could be used to predict optimal and safe dose ranges of vericiguat for Phase 2b studies in patients with worsening chronic HF. This novel bridging approach was applied in one of several translational stages to accelerate the development of vericiguat (Figure 1). Purpose: We used prior knowledge from other sGC stimulators in a combined PK/PD and PBPK modelling approach to directly initiate Phase 2b studies of vericiguat in patients after Phase 1 studies in healthy volunteers. Methods: PK, heart rate (HR) and systemic vascular resistance (SVR) data for vericiguat, nelociguat and riociguat were used to calculate PK/PD slopes of linear models, corrected with fraction unbound percentages (2.2%, 3.6% and 3.9%, respectively), to compare potency relative to riociguat based on unbound concentrations. PK estimates for nelociguat and riociguat were derived using population PK modelling (NONMEM) from patient studies with sparse PK sampling. PBPK models informed by preclinical physicochemical and PK data as well as clinical data for vericiguat were used to predict vericiguat PK in patients with HF (PK-Sim). Exposure–response data for riociguat in patients indicated the optimal range of PD responses for vericiguat (blood pressure for safety and cardiac index for efficacy). Results: Vericiguat and nelociguat had lower potency than riociguat when comparing PK/PD slopes for HR and SVR (slope ratios of 0.23–0.32 for vericiguat and 0.33–0.47 for nelociguat). Plasma concentrations of vericiguat would need to be ∼3.6 times that of riociguat for equivalent responses. In patients with PH and LVD the optimal plasma concentration range for riociguat was ∼10–100 μg/l in exposure–response and safety studies, which translates to a target exposure range of ∼90–900 μg/l for vericiguat in patients with HF. PBPK modelling showed that vericiguat 2.5 mg and 10 mg would cover the target exposure range and that 1.25 mg would be a "non-effective" dose level with respect to haemodynamics. Conclusions: Our novel translational approach combining popPK/PD analyses of other sGC stimulators with PBPK modelling enabled vericiguat to move directly from Phase 1 to Phase 2b, reducing development time by ∼2 years. PK and safety results from Phase 2b (SOCRATES-REDUCED) and Phase 3 (VICTORIA) trials confirmed that use of this translational approach to predict dose ranges of vericiguat was successful. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Funding for this research was provided by Bayer AG, Berlin, Germany